The processing and properties of syntactic Al foams containing low cost expanded glass particles - Wright, Andrew; Kennedy, Andrew R. (Wiley, 2016)
Expanded glass particles (EGP) are used to manufacture Al syntactic foams using a simple vacuum casting method. Clamping of the casting in the stainless steel mold is observed when preheating the mold to >400 C, causing damage to the EGP, resulting in a weaker foam but with the significant advantage of eliminating the yield drop, improving the energy absorption characteristics. The same effect in castings that are not clamped (for mold preheats <400 °C) can be achieved by quenching in liquid nitrogen. These “low strength” syntactic metal foams are a cost-effective alternative to metal foams and porous metals (in terms of specific strength, stiffness, and energy absorption) rather than “conventional” syntactic foams which contain smaller, stronger, hollow microspheres.